The Rickettsia type IV secretion system: unrealized complexity mired by gene family expansion. Issue 6 (14th June 2016) - Gillespie, Joseph J.; Phan, Isabelle Q. H.; Driscoll, Timothy P.; Guillotte, Mark L.; Lehman, Stephanie S.; Rennoll-Bankert, Kristen E.; Subramanian, Sandhya; Beier-Sexton, Magda; Myler, Peter J.; Rahman, M. Sayeedur; Azad, Abdu F.
Abstract : Many prokaryotes utilize type IV secretion systems (T4SSs) to translocate substrates (e.g. nucleoprotein, DNA, protein) across the cell envelope, and/or to elaborate surface structures (i.e. pili or adhesins). Among eight distinct T4SS classes, P-T4SSs are typified by the Agrobacterium tumefaciens vir T4SS, which is comprised of 12 scaffold components (VirB1–VirB11, VirD4). While most P-T4SSs include all 12 Vir proteins, some differ from the vir archetype by either containing additional scaffold components not analogous to Vir proteins or lacking one or more of the Vir proteins. In a special case, the Rickettsiales vir homolog ( rvh ) P-T4SS comprises unprecedented gene family expansion. rvh contains three families of gene duplications ( rvhB9, rvhB8, rvhB4 ): RvhB9, 8, 4-I are conserved relative to equivalents in other P-T4SSs, while RvhB9, 8, 4-II have evolved atypical features that deviate substantially from other homologs. Furthermore, rvh contains five VirB6-like genes ( rvhB6a – e ), which are tandemly arrayed and contain large N- and C-terminal extensions. Our work herein focuses on the complexity underpinned by rvh gene family expansion. Furthermore, we describe an RvhB10 insertion, which occurs in a region that forms the T4SS pore. The significance of these curious properties to rvh structure and function is evaluated, shedding light on a highly complex T4SS. Abstract : Species of Rickettsia contain a strange type IV secretion system that is rich in gene duplication, indicating remarkable structural and functional complexity for a bacterial translocation machine. Abstract :